2013
DOI: 10.22610/jsds.v4i3.740
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Business Management: A Practical Framework and Causal Model of Empowering Leadership, Team Cohesion, Knowledge-Sharing Behavior, and Team Performance

Abstract: Research objectives were to determine a practical framework and to create a causal model of empowering leadership, team cohesion, knowledge-sharing behavior, and team performance of petroleum refinery plant employees in Thailand. The study reported the responses of 594 operational employees from seven petroleum refinery plants operating in different parts of Thailand. Data were analyzed with descriptive statistics using SPSS (version 11.5) and path analysis using LISREL (version 8). Research findings indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 54 publications
1
7
0
2
Order By: Relevance
“…Knowledge sharing behavior has a positive mediative effect on the relationship between leadership empowerment and team performance. Also, knowledge sharing behavior positively mediates the relationship between team cohesion and team performance (Kasemsap, 2013). The results reinforce that a cohesive team enables knowledge sharing and task cohesion among members.…”
Section: Cohesion and Proactive Knowledge Sharingsupporting
confidence: 64%
“…Knowledge sharing behavior has a positive mediative effect on the relationship between leadership empowerment and team performance. Also, knowledge sharing behavior positively mediates the relationship between team cohesion and team performance (Kasemsap, 2013). The results reinforce that a cohesive team enables knowledge sharing and task cohesion among members.…”
Section: Cohesion and Proactive Knowledge Sharingsupporting
confidence: 64%
“…We postulate that empowering leadership can enhance person-group fit. In terms of the need for belongingness, according to Arnold et al (2000) , the coaching behavior encouraging employees to solve problems, thereby providing them with opportunities to improve team cohesion and form collective team identification ( Kasemsap, 2013 ). Second, empowering leadership creates opportunities for employees to participate in decision-making which promotes the chance for employees to engage in team work and create team-based commitment.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…If members do not communicate, the unique ideas of each member will not be shared. Communication has remarkable effect on team performance (27). Prior studies found positive relationship between team cohesion and performance (27,28).…”
Section: Results and Findingsmentioning
confidence: 98%
“…Communication has remarkable effect on team performance (27). Prior studies found positive relationship between team cohesion and performance (27,28). Hence this study included task interdependence, team communication, and team cohesion in the proposed conceptual model.…”
Section: Results and Findingsmentioning
confidence: 98%